Modal Intelektual, Nilai Perusahaan, dan Manajemen Risiko sebagai Variabel Moderasi - Putri, Ni Komang Shinta Rani; Wirajaya, I Gde Ary (E-Jurnal Akuntansi; Vol 33 No 11 (2023), 2023)
The purpose of this study was conducted to find out, analyze, and obtain empirical evidence regarding the effect of intellectual capital on firm value with risk management as a moderating variable and firm size as a control variable. The theory used in this research is signal theory and resource theory. The population used in this study are all banking companies that are registered and listed on the Indonesia Stock Exchange for the 2019-2021 period. The sampling technique used was purposive sampling method and the number of samples obtained was 69 observations. The data analysis technique used is Moderated Regression Analysis. The results of this study indicate that intellectual capital has a positive effect on firm value, risk management is able to strengthen the positive influence of intellectual capital on firm value. Kata Kunci: Profitabilitas; Ukuran Perusahaan; Growth; CSR DisclosureKeywords: intellectual capital; firm value; risk management